THE PURPOSE OF LAW, PANCASILA AND LEGALITY ACCORDING TO ERNST UTRECHT: A CRITICAL REFLECTION - Manullang, Fernando Morganda (Indonesia Law Review, 2015)
Ernst Utrecht is one of the best legal scholars Indonesia has ever had. His political views position him as an organic intellectual; a legal scholar involved in and expressing the social consciousness, both in the academic as well as in the political arena. His controversial involvement came to a tragic end, causing him to leave Indonesia for good. This article describes and reflects on some of Utrecht’s rather controversial ideas about law and politics; namely, first, “pengayoman” (guardianship) the purpose of law in Indonesia, a purpose of law which is almost completely absent from the mainstream conception of the purpose of law in contemporary legal texts, as he relates it to the idea of revolution and the teaching of Marxism, albeit taking a more critical approach. Second, Pancasila as state ethics and grundnorm, a theme which remains debated up to the present time, in spite of Kelsen’s express statement that grundnorm must be clean from non-legal elements, thus the implication of recognizing Pancasila as state ethics is that Pancasila as grundnorm loses its theoretical ground. Finally, the principle of legality, subject to Utrecht’s strong critique for reflecting the interest of those in power only. All of his above described thinking undoubtedly reaffirm Utrecht’s predicate as one of the best legal scholars Indonesia has ever had.